Whose Immortality Is It Anyway? The Hungarian Translations of Shakespeare’s Sonnet 18 - Egri, Péter (FOCUS: Papers in English Literary and Cultural Studies, 1998)
Text and translation mutually function as one another’s context both in terms of style and cultural history. None of Shakespeare’s sonnets is easy to translate, but Sonnet 18 would seem to be especially difficult to render. The turns of its intellectual-emotional structure, the dramatic changes of its poetic message, the verse music of its rhyme scheme, the referential ambiguities of the sonnet, the relationship between sense and sound, metre and rhythm, the intricacies of imagery and the daringly innovative treatment of tradition present and represent complexities that test the translator, try the adventurer, and challenge the challenger.